Estudio de factibilidad para la creación de una empresa de postes a base de plástico no reciclable y concreto en la ciudad de Tunja Boyacá - Palacio Lesmes, Andrea Milena; Camacho Numpaque, Yeimi Camila (Universidad Antonio Nariño, 2021)
The objective of this project is the feasibility study of a company that produces fenceposts based on concrete and non-recyclable plastic, in the city of Tunja Boyacá. The purpose is totake advantage of plastics that do not yet have a transformation because they are mixtures of plastics with other materials, some of these materials are potato packages, candy wrappers, straws, among others, and in Colombia it is 93% of those that are not recycled that are located in section 7 (others) in the plastic classification table, on the other hand, the durability of PVC plastic poles that already exist will be improved in their resistance, which are the disadvantagesof this product.